Interface-Based Software Development - Rais, Aziz; Pecinovský, Rudolf, 1954-; Lacko, Branislav; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2017)
Even though there are many software development and project management methodologies available, research and practice both show that IT software development projects still fail, and that the quality of software products does not always meet customers' expectations. There might be multiple causes for such failures, but some of these reasons can be seen to influence or create others. Therefore, the larger the project is, the higher its risk of failure, especially if the teams involved work remotely (distributed and outsourced). This increase in project complexity is considered the motivation for this paper. Similarly, there are other factors that can result in a project's failure and customers' dissatisfaction regarding software quality. All such factors identified by research conducted by organizations specializing in this area are analyzed in order to identify a common root of IT project failures. Once the root causes of these failures have been identified and analyzed, the goal of the Interface based software development methodology is to solve them. The solution offered by an Interface based software development methodology is to improve understanding of software requirements and to describe these requirements with interfaces in an object-oriented way. Interface based software development will support and drive development towards service-oriented architecture (SOA) and component-based development (CBD). The goal of interface based software development is to increase software testability and maintainability and to make it more easily feasible to execute various software development processes in parallel.
Vedoucí práce: Rudolf Pecinovský
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: informatika [obor disert. práce]; disertace; dissertations